The Application of Graphology in Assessing Deaf People's Communication and Social Interaction Abilities - Zebua, Dinna Rahmayani; Wirtati, Ira (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2024)
Graphology, the study of handwriting, has been used to interpret an individual's character and personality. This study examined the application of graphology in assessing the communication and social interaction abilities of deaf people. Deaf individuals face challenges in building social relationships and communicating with others because of their hearing impairment and reliance on nonverbal communication techniques such as sign language. Previous research has explored the potential of graphology in diagnosing attention deficit hyperactivity disorder (ADHD) and mental retardation as well as in revealing the psychological aspects of historical figures. However, few studies have investigated the application of graphology in assessing the counseling needs of deaf individuals. This study employed a qualitative approach to analyze the handwriting samples of deaf participants using graphological techniques. The findings revealed that intensifying and reducing signs in the handwriting of deaf individuals influenced their communication and social interaction abilities. This study highlights the potential of graphology as an alternative assessment tool for understanding the characteristics and conditions of deaf individuals, without relying on oral communication. These results contribute to the field of counseling by providing insights for assessors, such as psychologists and counselors, to develop appropriate interventions and approaches tailored to the unique needs of deaf individuals. Further research is recommended to explore the effectiveness of graphology-based interventions in enhancing communication and social interaction skills of deaf individuals.